Mental health literacy in adolescents: A systematic literature review - Afendy, Popy Mayasari; Ahman, Ahman; Setiawati, Setiawati; Nadhirah, Nadia Aulia (Universitas Negeri Yogyakarta, 2024)
Adolescent mental health literacy (MHL) plays a critical role in equipping young individuals to make informed health decisions and seek appropriate care. This study aimed to explore the level of adolescent MHL worldwide, its influencing factors, and effective strategies to improve it through a systematic review of 10 selected studies published between 2000 and 2024. Using PRISMA guidelines, relevant articles were identified from databases including Scopus, PubMed, and Google Scholar. Key findings indicated significant variability in MHL among adolescents globally, influenced by factors such as education, culture, and access to information. While adolescents were generally better at recognizing common conditions like depression, less than 50% could identify it accurately. Gender disparities were observed, with females more likely to recommend professional help. Effective interventions, such as school-based programs, showed promise in enhancing MHL, particularly in improving knowledge and reducing stigma. Instruments such as the Mental Health Literacy Questionnaire and The Friend in Need Questionnaire were commonly used for assessment, although reliance on self-reported data highlights the need for more objective tools. The findings underscored the importance of comprehensive health education programs in schools, covering topics such as mental health, nutrition, and healthy lifestyles, to bridge knowledge gaps and foster help-seeking behaviors. This study concluded that addressing disparities in adolescent MHL through tailored, multi-sectoral approaches, including education, community engagement, and policy reforms, was essential to empower adolescents globally and improve public mental health outcomes.